Equine digital tendons show breed‐specific differences in their mechanical properties that may relate to athletic ability and predisposition to injury. (23rd September 2019) - Verkade, M. E.; Back, W.; Birch, H. L.
Summary: Background: Throughout the ages, human subjects have selected horse breeds for their locomotor capacities. Concurrently, tissue properties may have diversified because of specific requirements of different disciplines. Objectives: The aim of this study was to compare the biomechanical properties of tendons with different functions between equine breeds traditionally selected for racing or sport. Study design: This study used ex vivo tendons and compared the mechanical properties of the common digital extensor tendon (CDET) and superficial digital flexor tendon (SDFT) between racehorses (Thoroughbred [TB]) and sports horses (Friesian Horse [FH], Warmblood [WB]). Methods: The SDFT and CDET of FH (n = 12), WBs (n = 12) and TBs (n = 8) aged 3–12 years were harvested. The cross sectional area (cm 2 ), maximal load (N), ultimate strain (%), ultimate stress (MPa) and elastic modulus (MPa) were determined and tested for significant differences between the breeds (P<0.05). Results: The SDFT from WB horses had a significantly lower elastic modulus than TB horses and failed at a higher strain and load than both FHs and TBs. The mechanical properties of the CDET did not differ between breeds. In agreement with previous studies, the CDET failed at a higher stress and had a higher elastic modulus than the SDFT and, for the WB group of horses only, failed at a significantly lower strain. Interestingly, the mode of failure differed between breeds, particularly with respect to the FHs. Main limitations: The exercise history of horses used in this study was unknown and the age‐range was relatively large; both these factors may have influenced the absolute properties reported in this study. Conclusions: This study shows for the first time that mechanical properties of the SDFT differ between breeds. These properties are likely to be related to selection for high‐speed vs. an extravagant elastic gait and may be an important indicator of performance ability. The Summary is available in Spanish – see Supporting Information